1980
DOI: 10.1002/j.1556-6978.1980.tb01622.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex and Conceptual Level Empathic Responses to Ambivalent Affect

Abstract: Four variables (helper conceptual level, helper sex, client sex, and type of client affect), their interactions, and effects on empathic ability were examined. All undergraduate “helpers” had been trained in empathic response and were asked to respond empathically to videotaped role‐playing “clients.” Client videotapes were equally divided among male and female clients, and among ambivalent and nonambivalent affect states. A significant interaction was found between helper conceptual level and type of client a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…A study by Handley (1982) showed that differences in cognitive information organization affected the way in which counselors and supervisors made interpretations and communicated about the clients they were seeing. Kimberlin and Friesen (1980) also found a relationship between restricted levels of cognitive complexity in counselors and a difficulty responding to complex affect. Participants who had higher levels of conceptualizing skill demonstrated less difficulty responding to complex affective client presentations.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…A study by Handley (1982) showed that differences in cognitive information organization affected the way in which counselors and supervisors made interpretations and communicated about the clients they were seeing. Kimberlin and Friesen (1980) also found a relationship between restricted levels of cognitive complexity in counselors and a difficulty responding to complex affect. Participants who had higher levels of conceptualizing skill demonstrated less difficulty responding to complex affective client presentations.…”
mentioning
confidence: 80%
“…Kimberlin and Friesen (1980) also found a relationship between restricted levels of cognitive complexity in counselors and a difficulty responding to complex affect. Participants who had higher levels of conceptualizing skill demonstrated less difficulty responding to complex affective client presentations.…”
mentioning
confidence: 83%
“…In all three studies, counselor trainees viewed videotapes of clients and made written counselor responses. Both Abramowitz, Abramowitz, and Weitz (1976) and Kimberlin and Friesen (1980) found female counseling students to be significantly more empathic than male students following empathy skills training. However, Carlozzi and Hurlburt (1982) reported no difference between male and female counseling students in affective sensitivity (empathy).…”
mentioning
confidence: 99%
“…Partial support for this matching procedure in counselor training has subsequently been reported. Kimberlin and Friesen (1980) found that low conceptual level trainees were less able to respond to complex affect than were high conceptual level trainees. They found that results from self-report measures supported in general the matching model, whereas behavioral measures did not.…”
Section: Cognitive Attributes and Counseling Performancementioning
confidence: 87%